ANALISIS FAKTOR-FAKTOR KESULITAN BELAJAR SISWA KELAS V PADA PEMBELAJARAN TEMATIK SD NEGERI 37 PEKANBARU - Yulita, Nanda; Putra, M. Jaya Adi; Zufriady, Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Learning difficulties are one of the obstacles in the learning process. This study aims to determine the factors that influence student learning difficulties in thematic learning in fifth grade elementary school students. The research location is at elementry school of 37 pekanbaru and the research was carried out in the even semester of 2019/2020. The type of research used in this research is qualitative research. This research uses a descriptive method. The sample in this study were students who experienced low student daily test scores when they finished completing one theme. Data collection was carried out using questionnaires and interviews. The results showed that students' interest in following the lesson was categorized as high, learning motivation with a percentage of 37% in the medium category, concentration with a percentage of 29% in the low category, habits with a percentage of 42% in the medium category, student intelligence with a percentage of 29% in the low category. , the family environment with a percentage of 29% in the low category, and the fact of the school environment with a percentage of 33% in the low category.Key Words: Learning difficultie, thematic learning, Elementry School of 37 Pekanbaru.